Pembinaan Keagamaan Disabilitas Autis Melalui Program Patas Talitis Di Kota Bukittinggi - Hanani, Silfia; Syafitri, Dian (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Religious guidance for individuals with autistic disabilities is an activity that provides religious knowledge to individuals with disabilities, facilitated through the Patas Talitis program conducted by the Ministry of Religion of the City of Bukittinggi. Meanwhile, this form of guidance is carried out to ensure that individuals with disabilities do not experience discrimination in the religious field, including religious guidance activities in the form of training and religious coaching provided to individuals with disabilities. The purpose of this guidance is to provide special attention and education to individuals with disabilities in the City of Bukittinggi, with the aim of enhancing the religious awareness of individuals with autistic disabilities, despite the limitations they may have. The method used in this service is qualitative descriptive. Through the Patas Talitis program, individuals with disabilities are guided in practical religious jurisprudence and moral faith activities, which are conducted for individuals with autistic disabilities, and are also carried out at Special Schools (SLB) specifically designed for autism. These religious development activities for individuals with disabilities have an impact on improving their religious awareness.